مكانة الأمن الاجتماعي في فقه مالك - مفتـــاح أحمــــد, ميـة (جامعة الوادي - University of Eloued, 2022)
إن القرآن الكريم والسنة النبوية الشريفة، لحافلان بالحديث عن توفير الأمن للأفراد والجماعات بمختلف أنواعه، إشعاراً لنا بضرورته، فلا استقرار ولا اطمئنان للتفرغ لعبادة الله سبحانه وتعالى، والسعي في شؤون الحياة وعمارة الكون دونه، لذا فهو مطلوب شرعاً للدارين الدنيا والآخرة. هذا البحث يتناول نماذج من فقه الإمام مالك بن أنس عن مراعاته لأمن المجتمع حفظاً لمقاصد الشارع؛ توزعت بين حفظ الدين والنفس والعرض والمال؛ وكان لحفظ النفس من جانبي الوجود والعدم الحظ الأوفر في الذكر والتمثيل، لأنه بالمحافظة عليها تحفظ بقية المقاصد؛ ومالك إنما هو مثال عن علمائنا رحمهم الله في اهتمامهم بذلك في فقههم وفتاويهم؛ عكس ما نعيشه اليوم من استهتار بالحق في الحياة - وما يتفرع عنه - عمداً أو تهاوناً. The Holy Qur’an and the Prophetic Sunnah are full of talking about security of all kinds to individuals and groups, notify us of its necessity, so there is no stability to devote itself to the worship of God Almighty and doing the affairs of life without him, so it is required by shari'a for the worldly and hereafter. This research deals with models from fiqh MALIK, on his considerate of social security, in order to protect objectives of shari'ah; the preservation of religion, the self, the honor, and the money. Preserving the self was the best of luck, because by preserving it preserves the rest of the objectives Malik is only an example of our scholars, in their taking care of them in jurisprudence and fatwas. The opposite of our reality today is a deliberate or negligent disregard for the life’s right - and its ramifications.
The position of social security in fiqh MALIK
مقال
Keywords: مكانة؛ أمن؛ مجتمع؛ مالك؛ مقاصد; position; security; society; Malik; maqasid.